Disharmoni Peraturan Penawaran Prioritas Wilayah Izin Usaha Pertambangan Khusus (WIUPK) Pasca Diprioritaskan Terhadap Badan Usaha Organisasi Kemasyarakatan “Keagamaan” - Salsabila, Ananda Putri (Jurnal Hukum & Pembangunan, 2025)
Abstract Priority offering of Special Mining Business License Areas (WIUPK) to business entities owned by religious community organizations without going through an auction process has caused legal polemics in Indonesia, especially after the enactment of Government Regulation (PP) Number 25 of 2024 concerning Amendments to Government Regulation Number 96 of 2024 2021 concerning Implementation of Mineral and Coal Mining Business Activities. This research aims to examine whether the policy is in accordance with applicable laws and regulations, especially in the context of implementing mineral and coal mining business activities. Apart from that, this research will also analyze the legal consequences that could arise if disharmony occurs in the regulations related to Special Mining Permit Areas (WIUPK), especially related to potential conflicts between applicable laws and regulations. One potential disharmony is related to the law. No. 3 of 2020 concerning Amendments to UU. No. 4 of 2009 concerning Mineral and Coal Mining. This research is doctrinal legal research using a statutory approach and a conceptual approach. Keywords: Disharmony, bidding, Special Mining Permit Area (WIUPK), Business Entity, Religious Community Organization, Auction